Influence of Positioning on Plain Levobupivacaine Spinal Anesthesia in Cesarean Section - Fabio Gori; Francesco Corradetti; Vittorio Cerotto; Vito Aldo Peduto (Anesthesiology Research and Practice)
Background. The behaviour of isobaric levobupivacaine in relation to gravity when used in obstetric spinal anesthesia is unclear. Methods. 46 women with ASA physical status 1 undergoing cesarean section were randomly allocated to 2 groups. Spinal anesthesia with 12.5 mg levobupivacaine was performed in the sitting position in all women. Those in the first group were placed in the supine position immediately after the injection, while those in the second group were asked to remain seated for 2 minutes before assuming the supine position. The sensory block level, the onset of sensory and motor blocks, the regression of the sensory block for 2 dermatomes of the sensory block, the first request for analgesics, and the regression of motor block were recorded. Results. No differences in onset times, sensory level, or Bromage score were observed between the two groups. The time of first analgesic request was earlier in the seated group (supine 131±42 min, seated 106±29 min, 𝑃=.02). Conclusion. Isobaric levobupivacaine in women at term produces a subarachnoid block the dermatomal level of which does not depend on gravitational forces.